German soldiers in Latvian SSR war captive camps: reflections of problems in soviet represive structures documents - Bambals , Ainars (Genocidas ir rezistencija, 2015)
The aim of this article is to provide research insights on the topic of German prisoners of war in Latvia (1945–1950). Research objectives: 1) to examine the sources; 2) to investigate the situation of German prisoners in the prisoner-of-war camps on the territory of the Latvian SSR; and 3) to investigate the problems of researching the historical source – the USSR NKVD German prisoner-of-war cemetery books.
Keywords: Latvia; german occupation; soviet regime; soviet concentration camps